Basis Assets - Ahn, Dong-Hyun; Conrad, Jennifer; Dittmar, Robert F. (Review of Financial Studies, 2009)
This paper proposes a new method of forming basis assets. We use return correlations to sort securities into portfolios and compare the inferences drawn from this set of basis assets with those drawn from other benchmark portfolios. The proposed set of portfolios appears capable of generating measures of risk–return trade-off that are estimated with a lower error. In tests of asset pricing models, we find that the returns of these portfolios are significantly and positively related to both CAPM and Consumption CAPM risk measures, and there are significant components of these returns that are not captured by the three-factor model.